THEORETICAL СONСEPTUАLІZАTІON OF BАNKІNG RІSK MАNАGEMENT - O. Kuzmak; O. Kuzmаk; V. Bіlyk (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The article explore the theoretical aspects of banking risk management, its purpose, objects, subjects and advantages are singled out. Effective banking risk management should be considered as the main task of banking institutions in their development. From this research of theoretical foundations of banking  risk management, we consider it а new direction of scientific  research in Ukraine, so the theoretical and methodological developments of these problems are  relevant today. In order to solve these problems, we propose to distinguish between «management of banking risks» and «banking risk management». In the research of the theoretical foundations of banking risk management, the interpretation of these basic concepts was proposed. Consequently, the authors proposed defined «management of banking risks» as a process that includes methods and techniques for identifying, assessing, monitoring, controlling and forecasting bank risks, in order to achieve the main objectives of the banks. And «banking risk management» defined as а set of principles, means and forms of management of the bank’s activities related to risks. For the development of the theory of banking risk management the authors proposed identified and characterized his subjects and objects. It is determined that the object is risks of banks and economic relations at risk, and the subject is the employees of the structural units, which, through the application of knowledge, skills, information and financial resources, participate in the management of banking risks. In addition, the advantages of effective risk management in the activities of banks are determined. The lack of research on the theoretical aspects of banking risk management can lead to deepening of theoretical and methodological problems and may negatively affect in the practical activities of banks.